Receptor conversion in distant breast cancer metastases - Hoefnagel, Laurien DC (BioMed Central, 2010)
INTRODUCTION: When breast cancer patients develop distant metastases, the choice of systemic treatment is usually based on tissue characteristics of the primary tumor as determined by immunohistochemistry (IHC) and/or molecular analysis. Several previous studies have shown that the immunophenotype of distant breast cancer metastases may be different from that of the primary tumor (receptor conversion), leading to inappropriate choice of systemic treatment. The studies published so far are however small and/or methodologically suboptimal. Therefore, definite conclusions that may change clinical practice could not yet be drawn. We therefore aimed to study receptor conversion for estrogen receptor alpha (ERα), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) in a large group of distant (non-bone) breast cancer metastases by re-staining all primary tumors and metastases with current optimal immunohistochemical and in situ hybridization methods on full sections. METHODS: A total of 233 distant breast cancer metastases from different sites (76 skin, 63 liver, 43 lung, 44 brain and 7 gastro-intestinal) were IHC stained for ERα, PR and HER2, and expression was compared to that of the primary tumor. HER2 in situ hybridization (ISH) was done in cases of IHC conversion or when primary tumors or metastases showed an IHC 2+ result. RESULTS: Using a 10% threshold, receptor conversion by IHC for ERα, PR occurred in 10.3%, 30.0% of patients, respectively. In 10.7% of patients, conversion from ER+ or PR+ to ER-/PR- and in 3.4% from ER-/PR- to ER+ or PR+ was found. Using a 1% threshold, ERα and PR conversion rates were 15.1% and 32.6%. In 12.4% of patients conversion from ER+ or PR+ to ER-/PR-, and 8.2% from ER-/PR- to ER+ or PR+ occurred. HER2 conversion occurred in 5.2%. Of the 12 cases that showed HER2 conversion by IHC, 5 showed also conversion by ISH. One further case showed conversion by ISH, but not by IHC. Conversion was mainly from positive in the primary tumor to negative in the metastases for ERα and PR, while HER2 conversion occurred equally both ways. PR conversion occurred significantly more often in liver, brain and gastro-intestinal metastases. CONCLUSIONS: Receptor conversion by immunohistochemistry in (non-bone) distant breast cancer metastases does occur, is relatively uncommon for ERα and HER2, and is more frequent for PR, especially in brain, liver and gastro-intestinal metastases.